Thermal Steganography: A New Way to Steal Data from Air-Gapped Computers Using Heat and Fan Noise - Kaushal D Jani; Bhargav Rajyagor (International Journal of Information Security Engineering, 2026)
Nowadays, high-security computers are "air-gapped," meaning they are not connected to the internet to prevent hacking. Cybercriminals are increasingly using direct, physical methods to access and take data instead of relying on internet-based attacks. This paper introduces a new cybersecurity threat called Thermal-Secret. Most existing heat-based attacks are very slow and fail if the room temperature changes. To solve this, we developed a Slope-Based method. Instead of looking at how hot a computer is, we look at how fast the temperature is rising or falling.In our experiment, we used a special Python script that makes the CPU do heavy math (Matrix Multiplication). This creates a "Heat Signal" that represents binary 1s and 0s. A "1" is sent by making the CPU hot quickly, and a "0" is sent by letting it cool down. We monitored these changes using the computer’s own internal sensors and fan speed data.Our testing shows that this method is very hard for Antivirus software to detect because it looks like a normal computer task. Even if the computer has strong fans, our "Slope" method can still read the hidden message correctly. This research proves that even if a computer is not on the internet, its heat can be used to leak secret information. We conclude that companies must start "masking" their thermal data to protect themselves from such advanced physical hacking attacks.
Keywords: Air-Gapped Systems; Covert Channels; Differential Slope-Based Modulation; Thermal Steganography; slope-based Steganography